Porous tricalcium phosphate produced using polyurethane foam template for artificial bone graft application - Fariza binti Abdul Rahman (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Artificial bone graft has become a favourable solution for bone substitute, replacing the function of autograft and allograft. Due to this, study on the development of porous artificial bone graft has risen rapidly in line with the demand. The critical part of this development falls on the issues of fabricating porous structure with high interconnectivity while maintaining its mechanical strength. The purpose of this study is to produce porous tricalcium phosphate (TCP) utilising low-cost polyurethane (PU) foam as template for bone graft substitute. TCP, which is one of the calcium phosphate families, has been chosen due to its salient property that is highly resorbable upon its application. In addition, low-cost PU foam or kitchen foam is utilised as a structural guide. Foam impregnation method was selected based on its ability to form three-dimensional porous bodies with a simple procedure and able to produce well-distributed porosity. The experiment started with the production of TCP slurry by mixing the TCP powder at controlled amounts of loading at 12, 13, 14, 15 and 16 grams with fixed amount of distilled water (25 grams). It was observed that, 13 grams of TCP powder was an adequate amount to produce good TCP slurry where the slurry was homogeneous and able to penetrate the PU foam, especially to impregnate the foam struts properly. Subsequently, the impregnated foam was dried at 24, 48, 72 and 96 hours at room temperature and ambient atmosphere to remove excess water inside it. The drying time of 72 hours demonstrated an enough time to prepare the impregnated foam before the sintering process. Two stages of sintering were done. The first stage was to remove the PU foam at 600°C with the rate of 5°C/min before executing 2 hours holding time was applied at this stage. It was then followed by powder densification at 1000, 1050, 1100, 1150 and 1200°C and the rate used was 10°C/min. Holding time was varied from 1, 2, 3 and 4 hours. Increase in sintering temperature and holding time had caused the grain growth of TCP. The optimum results were obtained at the sintering temperature of 1100°C with 3 hours holding time where the compressive strength was at 1.18 MPa with 35.9% porosity. The SEM macrograph of porous TCP block showed highly interconnected pores with an average pore size of 153 μm which are suitable to be applied as an artificial bone graft. The utilisation of the low-cost PU foam in foam impregnation method leads to the price reduction of porous TCP bone graft substitute which is well-known for its high price.